Impact of DBU on the synthesis of cellulose-graft-poly(l-lactide) copolymer in CO2 switchable solvent with different grafting strategies. (16th August 2021) - Lu, Shan; Li, Jinling; Liu, Fei; Chen, Meiling; Na, Haining; Zhu, Jin
Abstract: Modification of cellulose homogeneously by graft copolymerization via grafting-from or grafting-to approaches is an attractive and versatile way to impart specific properties onto this promising renewable material. The grafting efficiency is greatly influenced by the solvent and catalyst used during this process. In this study, cellulose- graft -poly (l -lactic acid) (C- g -PLLA) was prepared by ring opening polymerization of l -lactide (LA) (grafting-from) and transesterification of PLLA (grafting-to) with cellulose dissolved in CO2 switchable solvent. The impact of the presence of 1, 8-diazabicyclo-[5.4.0]-undec-7-ene (DBU) was then elucidated by comparing the grafting efficiency of the process with or without adding extra amount of this organic superbase. Results showed that without adding extra DBU, the grafting efficiency increased with an increase in concentration of grafting agents (LA or PLLA). However, when extra DBU was added, the grafting efficiency decreased with increased levels of DBU. These results indicate that the DBU protonated by the hydroxyl group from cellulose participated in the dissolution of cellulose after capture of CO2 in the switchable solvent, and played a role in the graft copolymerization to produce C- g -PLLA. On the other hand, the free DBU that was unprotonated displayed an antagonistic effect towards grafting copolymerization. Detailed graft copolymerization pathways and related modes of action were then considered in attempt to provide new insight into the role of CO2 switchable solvent for cellulose modification by ROP or transesterification. Graphical abstract: Dissolution of cellulose and grafting were promoted by DBU when it was protonated, but the grafting was inhibited when DBU was unprotonated. Image 1 Highlights: DBU played dual roles in cellulose dissolution and grafting copolymerization. The grafting-from strategy had better grafting efficiency than the grafting-to one. The ROP grafting of lactide onto the cellulose was achieved via AAP pathway. Transesterification grafting of PLLA onto the cellulose was inhibited by free DBU.